"Service Recovery: The Effects of Complaint Handling on Post-complaint Relationship Intention and Customer Switching Behaviour in the Taiwan Fastener Industry" - Hwang, Jui-Chin (2005)
Abstract In recent decades, many industries have started to realize the importance of relationship marketing and effective complaint handling as part of their customer retention strategies. This includes the traditional Taiwan fastener industry, which used to be considered as more technically focused rather than service-oriented. One of the main reasons for this industry to move toward a service orientation is that Taiwanese fastener trading companies have become highly customer-focused, providing excellent quality service to their overseas clients. As a result, the Taiwan fastener suppliers and manufacturers are expected to upgrade and improve their service quality in order to retain business from the trading company customers. In order to explore the aspects of service recovery in relation to future business relationship intentions and customer switching behaviour in the Taiwan fastener industry, qualitative research was conducted for this dissertation, with the adoption of several frameworks and ideas from previous research in the field. This includes the influence of perceived justice on customer satisfaction within the complaint handling process (Tax, Brown, and Chandrashekaran 1998), the effects of customer satisfaction to relationship intentions (Coulter and Ligas 2000; Kumar, Bohling and Ladda 2003), and possible factors leading to service switching behaviours (Keaveney, 1995).